The Provenance of the Transcript of Gong Yang Shu in the Hosa Library—Including Problems Concerning the Original Edition of Kanazawa Library and the Revised Editions from the Song and Yuan Dynasties in Chuanshu Tang - Jie Shi (Journal of Library and Information Studies)
The manuscript of Gong Yang Shu (公羊疏) from the late Muromachi period, housed in the Hosa Library (蓬左文庫) in Japan, is the only complete Dan Shu Ben (單疏本) in the world. According to the newly discovered Marginalia and Proofread Edition (校宋本) by Hayashi Razan (林羅山), Hayashi and his son collated the Wan Li Bei Jian Ben (萬曆北監本) based on the Dan Shu Ben held in the Kanazawa Library (金澤文庫) in 1654. This suggests that the original loss at Kanazawa occurred before 1654. The Hosa Edition (蓬左本) of Gong Yang Shu, now preserved, was copied from the original edition of the Imperial Academy’s reprint of the Southern Song Dynasty, which was housed in the Kanazawa Library. The Gong Yang Shu in the Kanazawa Library was not revised during the Song and Yuan Dynasties but predates the seven volumes of the extant edition held in the National Library of China today. A comparison with the remnants of the Revised Edition (遞修本) reveals that the variants in the Hosa Edition are superior to those in the Revised Edition. The disorganized sections of the Hosa Edition can be supplemented using the Revised Edition, and any missing or inaccurately copied parts of the Hosa Edition can also be corrected with reference to the Revised Edition. A comprehensive use of the two Dan Shu Ben editions, along with Hayashi Razan’s Marginalia and Proofread Edition, is highly beneficial for the collation and study of Gong Yang Shu.